Utilization of the STEAM Method Through Loose Parts Media in the Learning Activities of Group B3 Children at TK Tunas Harapan, Baubau City - Malinda, Serli; Henny, Henny; Hartati, Hartati (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to describe the utilization of the STEAM (Science, Technology, Engineering, Art, and Mathematics) method through loose parts media in the learning activities of Group B3 children at TK Tunas Harapan, Baubau City. The background of this study is based on the lack of variation in learning media and the minimal active involvement of children in the learning process, which affects the development of their creativity and independence. The research method used is descriptive qualitative with a Participatory Action Research (PAR) approach. The research subjects consisted of 10 children aged 5–6 years. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study show that the application of the STEAM method using loose parts media—such as water propagation experiments, stamping color, painting, color mixing, and creating artworks using recycled materials—can increase children’s active involvement, creativity, problem-solving abilities, and socio-emotional skills. Children were more enthusiastic, explorative, and independent in completing learning tasks. Thus, the application of the STEAM method through loose parts media is proven effective as an innovative approach in early childhood education.